“The face of the Singaporean woman : a qualitative research study on the beauty construction of Indian women and their negotiations with Singaporean beauty narratives.” - Visvanathan, Shobanu (2018)
The purpose of this research study is to evaluate the beauty construction of Singaporean Indian women, by analysing their interactions with two conflicting beauty narratives – light-skinned beauty and national beauty – proliferated in Singapore. With both narratives contested on skin colour, this paper delves into the experiences of Singaporean Indian women, who are perceived as a dark-skinned population. The 12 semi-structured interviews conducted, in this paper, explore the role of skin colour on their interactions with the identified beauty narratives, and highlight how they negotiate with them, to form their beauty identities. The findings point to the pervasiveness of the light-skinned beauty narrative in society, where skin colour plays an integral role in determining the access and opportunities for Singaporean Indian women to embody beauty. While Singaporean Indian women are generally underrepresented in beauty, access to both underlying aspects, differ according to pigment type, depriving dark-skinned Indian women from its embodiment. In terms of agency, alternative beauty narratives were recognised as a rich source for beauty construction.